Pemodelan Akreditasi SMK di Provinsi Banten dengan Menggunakan Logika Fuzzy Metode Mamdani - Syamsuri Syamsuri; Indiana Marethi (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2018)
This article aims to describe an accreditation model of vocational schools in Banten province that accredited for 2009-2011 using method of Mamdani of fuzzy logic. The data used were obtained from Banten Accreditation Board for Schools/Madrasah (BAP-S/M), 275 expertise in vocational programs are accredited by the BAP-S/M Banten during 2009-2011. In the accreditation model using fuzzy logic assumes that: (1) there are strong correlation among content standards, process standards, competency standards, and assessment standards, so that we use score of process standards in modelling, (2) Standard educators and staff, as well as management standard strongly correlated, so that we choose educators, and (3) standards of infrastructure and financing have strong correlation, so that only one representing one standard, namely : standard of infrastructure. The model can be used in predicting the outcome of a vocational accreditation by just looking scores from the process standard, educators standard, and infrastructures standard. The resulting models have about 68% accuracy rate.